Morphological alteration of peritoneal mast cells and macrophages in the mouse peritoneal cavity during the early phases of an allergic inflammatory reaction - Oliani, S. M.; Lim, LHK; Christian, H. C.; Pell, K.; Das, A. M.; Perretti, M. (Academic Press Ltd, 2001)
We investigated the presence of mast cell granules in macrophages following an in vivo model of an allergic reaction. Injection of ovalbumin (100 mug) into the peritoneal cavity of sensitised mice produced a rapid (within 2 h) influx of neutrophils followed by a slower (after >4 h) eosinophil migration. Ovalbumin treatment induced a high incidence (similar to 50%) of mast cell degranulation compared to control phosphated-buffered saline-treated mice. The majority (similar to 90%) of peritoneal macrophages contained mast cell granules as early as 2 It post-ovalbumin, with lower values at later time-points, as determined by staining with Toluidine blue and Berberine sulphate. This was confirmed by electron microscopy which enabled us to identify the complex mast cell granule sub-structural components in macrophage phagosomes. In conclusion, we used histochemical and ultrastructural analyses to show that mast cell granules become internalised with macrophages during the early stages of an experimental allergic reaction. (C) 2001 Academic Press.
Keywords: mast cell granule; inflammation; phagocytosis; eosinophil; neutrophil